Contamination of Cockroaches (Insecta: Blattaria) by Medically Important Bacteriae: A Systematic Review and Meta-analysis. Issue 6 (20th June 2019) - Nasirian, Hassan
Abstract: Cockroaches have the potential to disseminate bacteria in their environments and therefore a systematic review and meta-analysis was conducted to assess the state-of-the-art of our knowledge regarding bacterial contaminants of cockroaches. At least 78 bacterial species and 42 genera from 24 families and 11 orders of bacteria were reported to have contaminated cockroaches. At least 61, 42, 12, 13, 7, and 16 bacterial species have contaminated Blattella germanica (L.) (Blattaria: Ectobiidae), Periplaneta americana (L.) (Blattaria: Blattidae), Blatta orientalis (L.) (Blattaria: Blattidae), Diploptera punctata (Eschscholtz) (Blattaria: Blaberidae), Periplaneta fuliginosa (Serville) (Blattaria: Blattidae), and Supella longipalpa (F.) (Blattaria: Ectobiidae), respectively. Blattella germanica is the most commonly contaminated cockroach species, with the widest bacterial species diversity that threatens human health, followed by P. americana . Cockroach bacterial contaminants may result in the dissemination of opportunistic or pathogenic infections, particularly nosocomial and foodborne infections. One-way analysis of variance (ANOVA) revealed significant differences between bacterial contaminant species of cockroaches, species of cockroaches with bacterial contaminants, cockroach body part surfaces from the point of view bacterial contaminants and countries of cockroach infested with bacterial contaminants ( P < 0.05). This statistical analysis indicates that the bacterial contaminants of the external cockroach body parts are potentially more harmful than from internal surfaces, and secondly, the bacterial contaminants of cockroaches in hospital environments are potentially more harmful than from other human environments. The survey indicated that the bacterial contaminant species of cockroaches appear to be mostly multiple drug resistant. The challenges of cockroaches as being potential vectors of pathogenic or opportunistic agents of human infections are discussed.